Proton, Helium and Carbon Radiation Beam Targeting Reactive Oxygen, Nitrogen and Halogenated Species in TRIM-SRIM Model - Abdul Lateef, Zainab W (Al-Nahrain Journal of Science, 2012)
Nowadays proton beam radiation therapy is considered in few centers for management of malignancies. This study is aimed to explore the effect of proton, helium or carbon irradiation on free radicals. This study was conducted in Department of Physiology/Medical Physics, College of Medicine, Al-Mustansiriya University in Baghdad, Iraq during October 2009. TRIM-SRIM software version 1998 and 2003 were used for computed Bragg peak and for calculated the effect of proton, helium and carbon ions against free radicals related to oxygen, nitrogen and halogen species.The lowest stopping power near Bragg’s peak of proton targeting free radicals was against superoxide anion and its curve (the stopping power against energy) was shifted down while that of peroxynitrite (ONOO-) was shifted up. The stopping powers of helium targeting all studied free radicals were lower than corresponding proton irradiation but it required higher energy. Lower stopping power of carbon irradiation targeted hydroxyl (OH-) and halogenated radicals than the other reactive species were observed. It concludes that such form of external beam irradiation is associated with direct scavenging effect on free radicals of whatever sources.